Complexity in economics and beyond: Review paper - Durmus, Deniz (Heritage and Sustainable Development, 2021)
Complexity and complexity economics are relatively new fields of science, both of which started at the beginning of the 1980s. As it had emerged, questions have been raised regarding complexity’s applicability on human-involved systems and its predictive powers. Economics has been in the spotlight in recent years within the framework of complexity, since economics is one of the most well-established fields in social sciences. Within this framework, the field is referred to as complexity economics. While in its early years, complexity economics research had distanced itself from the reductionist neoclassic tradition of economics that has been identified by its use of, and reliance on, descriptive equations. One of the salient feature of complexity economics is its somewhat unorthodox approach to economic systems, as in its emphasis on non-equilibria. However in recent years, the proponents have become more assertive that complexity economics needs to be more modest and symbiotically co-exist with well-established mainstream economics. Although we focus on economics under the prism of complexity, our underlying interest is in the investigation of how other disciplines, such as industrial engineering and operations research, may benefit from a similar complexity-oriented perspective. Keywords: Complexity, complexity economics, mainstream economics, equation-based economics, non-equilibrium